Treatment of large intracranial aneurysms using the Woven EndoBridge (WEB): a propensity score-matched analysis - Musmar, Basel; Salim, Hamza Adel; Adeeb, Nimer; Aslan, Assala; Aljeradat, Bahaa; Diestro, Jose Danilo Bengzon; McLellan, Rachel M.; Algin, Oktay; Ghozy, Sherief; Dibas, Mahmoud; Lay, Sovann V.; Guenego, Adrien; et al. (Neurosurgical review, 2024)
The Woven EndoBridge (WEB) device is primarily used for treating wide-neck intracranial bifurcation aneurysms under 10 mm. Limited data exists on its efficacy for large aneurysms. We aim to assess angiographic and clinical outcomes of the WEB device in treating large versus small aneurysms. We conducted a retrospective review of the WorldWide WEB Consortium database, from 2011 to 2022, across 30 academic institutions globally. Propensity score matching (PSM) was employed to compare small and large aneurysms on baseline characteristics. A total of 898 patients were included. There was no significant difference observed in clinical presentations, smoking status, pretreatment mRS, presence of multiple aneurysms, bifurcation location, or prior treatment between the two groups. After PSM, 302 matched pairs showed significantly lower last follow-up adequate occlusion rates (81% vs 90%, p = 0.006) and higher retreatment rates (12% vs 3.6%, p < 0.001) in the large aneurysm group. These findings may inform treatment decisions and patient counseling. Future studies are needed to further explore this area.